A study on the fire resistance performance and thermal degradation behavior of a new intumescent flame retardant fluoroelastomer. (July 2014) - Ding, Shuai; Feng, Jie; Hao, Jianwei; Liao, Qiuheng
In order to improve the fire resistance of a fluoroelastomer when used as an insulating material, a combination of a triazine-based polymeric charring-foaming agent and ammonium polyphosphate as a novel intumescent flame retardant system was employed. The additional effect of zinc borate and modifying resins (ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, epoxy resin and ketone-aldehyde resin) on its fire resistance and thermal decomposition behavior was studied. Upon exposure to a 1000°C flame, the use of zinc borate and ketone-aldehyde resin reduced the backside temperature of intumescent fluoroelastomer-coated steel specimens, indicating a beneficial effect. Thermogravimetric, muffle furnace pyrolysis, scanning electron microscope and X-ray photoelectron spectroscope results revealed that the ketone-aldehyde resin adjusted the thermal decomposition temperature of the fluoroelastomer to match with that of the intumescent flame retardant-zinc borate system; in this way, the char residue formed was not only increased in quantity but also showed improved integrity and thermal stability.